FAKTOR-FAKTOR YANG MEMPENGARUHI PEMERINTAH DAERAH DALAM PENGANGGARAN - Fajri Hadi; Fatmayanti Fatmayanti (Universitas Teuku Umar, 2018)
This study aims to analyze the factors that influence the compliance of local governments to legislation in budgeting. The independent variables tested in this research are the legislative quantity, the amount of regional income, and the previous year opinion of Audit Board of the Republic of Indonesia (BPK). Dependent variables are tested using educational spending. This study uses secondary data derived from the financial audit report on the financial statements of district and municipal governments in the province of Aceh for the period of 2014 and 2015. The sample of research is 23 district and cities in Aceh Province every year. The total population was 46 districts and cities from 2 years of observation. The analysis method used is multiple linear regression analysis. The results showed that the legislative quantity (X1) the relationship designated by the coefficient B to respond to the legislative amount of 0.476, the regional income (X2) is pure income by looking at the level of coefficient B. The relationship designated by the B coefficient of regional income is 0.070, and the previous year opinion of the BPK (X3) based on the coefficient B to respond to the BPK opinion of 0.416, simultaneously and partially have a positive effect on the compliance of legislation.Keyword: Educational spending, amount of regional income, legislative quantity,previous year opinion of BPK..